Transformative Dynamics: Assessing the Impact of Digital Economy 4.0 on Human Resources Amidst the Covid-19 Pandemic in Indonesia - Herdian Candra Pradipta (IHSA Institute, 2023)
This research delves into the intricate interplay between Digital Economy 4.0 and the quality of human resources in Indonesia amidst the unprecedented challenges posed by the Covid-19 pandemic. Employing a mixed-methods approach encompassing in-depth interviews, surveys, and document analysis, the study navigates through a nuanced landscape, unraveling unexpected findings and illuminating transformative insights. The study uncovers a dichotomy in remote work satisfaction, revealing varied experiences that challenge traditional assumptions. Resilience and innovation emerge unexpectedly in certain traditional sectors, questioning established narratives about the impact of technological disruptions. Inclusivity challenges in remote regions present unexpected variations, prompting a call for targeted interventions to bridge digital divides. Government-industry collaborations, while impactful, exhibit varying degrees of influence, emphasizing the need for well-defined goals and sustained engagement. These findings contribute to a deeper understanding of the complexities inherent in the digital age and provide actionable implications for policies, education, and industry practices. The research concludes by emphasizing the dynamic nature of Digital Economy 4.0's impact on human resources, urging stakeholders to navigate the future with adaptability, innovation, and a commitment to inclusivity. The insights gleaned from this study offer a strategic foundation for shaping a digitally resilient and inclusive future for the Indonesian workforce.